2021
DOI: 10.1177/21514593211043961
|View full text |Cite
|
Sign up to set email alerts
|

MutiLoc Nail Versus Philos Plate in Treating Proximal Humeral Fractures: A Retrospective Study Among the Alderly

Abstract: Background Proximal humeral fractures (PHFs) account for 4–5% of all fractures in the elderly. There is still a controversy among the treatments in the displaced PHFs. Our aim was to explore the clinical outcome of PHFs with the treatment of MultiLoc nail or Philos plate in the elderly patients. Methods A total of 82 sustained elderly patients with PHFs were finally recruited between Dec 2016 and Dec 2017. 34 patients were treated with MultiLoc nail and 48 patients were treated with Philos plate. The demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…However, the varus group showed the largest NSA change of the three groups and, the NSA change in the plate group was significantly larger than in the medullary nail group, especially among the varus cases. This is similar to the findings of Bu et al 21 . which reflects the biomechanical advantage of the nail in resisting varus and rotational stresses.…”
Section: Discussionsupporting
confidence: 92%
“…However, the varus group showed the largest NSA change of the three groups and, the NSA change in the plate group was significantly larger than in the medullary nail group, especially among the varus cases. This is similar to the findings of Bu et al 21 . which reflects the biomechanical advantage of the nail in resisting varus and rotational stresses.…”
Section: Discussionsupporting
confidence: 92%
“…The straight intramedullary MultiLoc nail (Depuy Synthes) is a known third-generation intramedullary nail. Multiloc changed the design of the proximal 4–6° valgus angle of the second-generation intramedullary nail to that of a proximal straight nail [ 11 , 14 ]. The straight design theoretically leaves a safe zone between the lateral fracture fragment and the nail entry hole in the humeral head to avoid an unpredictable crack in this area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Multiloc intramedullary nail adds to the calcar screw design to provide better support for patients with large proximal medial cortical defects [ 19 ]. Several previous studies demonstrated the biomechanical advantages of the intramedullary nail [ 14 16 , 20 ]. There is a high risk of secondary displacement and fracture nonunion in elderly patients with poor bone quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 While most PHFs are minimally displaced or nondisplaced, for which conservative management is usually recommended, 1,5 controversy exists regarding optimal management of displaced and comminuted PHF. 6,7 There are a number of fixation techniques, such as tension-band routing, locking plate fixation, and intramedullary nailing over the past decade [8][9][10][11][12][13][14] ; however, no single technique demonstrated evidence-based superiority. Although locking plate fixation is considered as the standard treatment, complication rates are still unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%